A Hybrid Algorithm of Event-Driven and Time-Driven Methods for Simulations of Granular Flows (Communications in Computational Physics, 2011)
The classical discrete element approach (DEM) based on Newtonian dynamicscan be divided into two major groups, event-driven methods (EDM) and time-drivenmethods (TDM). Generally speaking, TDM simulations are suited for cases withhigh volume fractions where there are collisions between multiple objects. EDM simulationsare suited for cases with low volume fractions from the viewpoint of CPUtime. A method combining EDM and TDM called Hybrid Algorithm of event-drivenand time-driven methods (HAET) is presented in this paper. The HAET method employsTDM for the areas with high volume fractions and EDM for the remaining areaswith low volume fractions. It can decrease the CPU time for simulating granular flowswith strongly non-uniform volume fractions. In addition, a modified EDM algorithmusing a constant time as the lower time step limit is presented. Finally, an example ispresented to demonstrate the hybrid algorithm.